2013
DOI: 10.2478/s13533-012-0144-5
|View full text |Cite
|
Sign up to set email alerts
|

Sequence stratigraphic controls on reservoir characterization and architecture: case study of the Messinian Abu Madi incised-valley fill, Egypt

Abstract: Understanding sequence stratigraphy architecture in the incised-valley is a crucial step to understanding the effect of relative sea level changes on reservoir characterization and architecture. This paper presents a sequence stratigraphic framework of the incised-valley strata within the late Messinian Abu Madi Formation based on seismic and borehole data. Analysis of sand-body distribution reveals that fluvial channel sandstones in the Abu Madi Formation in the Baltim Fields, offshore Nile Delta, Egypt, are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Reference 12 showed that the incised-valley filling pattern of Abu Madi Formation is consistent with an abrupt relative sea-level fall followed by a still stand, then a progressive rise. For Abu Madi Formation reservoirs, the sections in the lower parts and upper parts consist of thick, porous sandstone, with some shale intercalations 13 .…”
Section: Geologic Settingsmentioning
confidence: 95%
“…Reference 12 showed that the incised-valley filling pattern of Abu Madi Formation is consistent with an abrupt relative sea-level fall followed by a still stand, then a progressive rise. For Abu Madi Formation reservoirs, the sections in the lower parts and upper parts consist of thick, porous sandstone, with some shale intercalations 13 .…”
Section: Geologic Settingsmentioning
confidence: 95%
“…It is difficult to identify the unconformity surface and ascertain the sequence boundary only by seismic reflections due to the relatively homogeneous property of the shale reservoir. Previous studies suggest that well-log data, geochemical parameters, lithofacies are of key significance for determining shale sequence boundaries [21,[53][54][55]. In this study, sequence boundaries are determined by a combination of redox indicator (U/Th ratio), well logs (Natural gamma ray, Uranium, Compensated neutron logging, Acoustic, Density), lithofacies.…”
Section: Identification Of Second-order Sequence Boundarymentioning
confidence: 97%
“…The regional tectonic setting of the area is characterized by an initial, syndepositional extensional rift phase, during which the Abu Roash F was deposited, followed by a phase of transtension and subsequently by a phase of transpression (Bayoumi & Lofty, 1989;Keeley & Wallis, 1991;Abd El Aziz et al 1998;El Toukhy et al 1998;Abdel-Fattah & Slatt, 2013;Sarhan, 2017;Abdel-Fattah et al 2021). During the entire tectonic history up to the present day, the maximum horizontal stress has been oriented NW-SE (Bayoumi & Lofty, 1989;Sarhan, 2017).…”
Section: B Regional Settingmentioning
confidence: 99%